2016
DOI: 10.1002/admt.201600194
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Toward Self‐Powered Papertronics: Integrating Biobatteries into a Single Sheet of Paper

Abstract: A stackable and 3D manufactured bacteria‐powered battery is constructed within a single sheet of paper for on‐chip, disposable paper‐based electronics or “papertronics.” The manufacturing technique on paper greatly reduces fabrication time and cost of the biobatteries and revolutionizes their potential use as a disposable power source in remote and resource‐limited regions for self‐powered papertronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…With the further decrease in external resistance with 8 kΩ, the MFC suffered from the mass transfer loss of anolyte needed to provide more organic food to the bacteria, limiting current production. The produced power and current densities were six times and eight times higher, respectively, than those of our previous dual‐textile‐layer MFC and are comparable with or even higher than other flexible MFCs …”
Section: Resultssupporting
confidence: 58%
“…With the further decrease in external resistance with 8 kΩ, the MFC suffered from the mass transfer loss of anolyte needed to provide more organic food to the bacteria, limiting current production. The produced power and current densities were six times and eight times higher, respectively, than those of our previous dual‐textile‐layer MFC and are comparable with or even higher than other flexible MFCs …”
Section: Resultssupporting
confidence: 58%
“…The detailed fabrication processes for the air cathode on paper were reported in our previous reports [24][25][26]. In short, 15 mg·cm −2 AC catalysts with a binder solution were brushed on the wax-based PEM, and subsequently air dried for 24 h ( Figure S1).…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…The anodic tab was engineered to have a conductive and hydrophilic feature with a carbon current collector, while the cathodic tab was composed of a wax-based PEM, an air-cathode catalyst layer, and a nickel current collector ( Figure S2). Previously, many studies demonstrated that the wax-based PEM can work as an ion exchange membrane, separating the anodic part from the cathode while allowing protons to pass through [18,19,25,26]. The cathodic surface was exposed to the air for a maximized cathodic reaction, and a hole was made through the entire cathodic tab to allow the sample to be introduced to the anode after folding.…”
Section: Power Generation From a Single Mfc Unitmentioning
confidence: 99%
See 2 more Smart Citations